PENGELOLAAN PARTICIPATING INTEREST 10% (SEPULUH PERSEN) DALAM RANGKA MENINGKATKAN KESEJAHTERAAN DI KABUPATEN SIAK - H, Juanda Hasanuddin; Firdaus, Firdaus; Jayakusuma, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
One of the strategic issues in managing the upstream oil and gas sector in Indonesia isthe obligation to bid Participating interest of 10% (ten percent) by the KKKS managing an Oiland Gas Working Area to the Regional Owned Enterprise (BUMD) at the operational location.involvement of regional governments in the form of responsibility for giving appointments toBUMDs or regional companies in order to obtain 10% PI management which is expected tobe able to provide profits or profits that will increase regional income for the welfare of localcommunities. Apart from that, it is hoped that it will be able to provide knowledge andexperience of cooperation for BUMDs in managing oil and gas working areas as a contractor.The type of research in this thesis uses sociological legal research, namely research onthe effectiveness of law in society. The nature of this thesis research is research descriptivewhich systematically describes the facts and characteristics of the object being studiedaccurately. The data collection technique in this research is the interview method and literaturereview, then after the data is collected it is then analyzed to draw conclusions.Management Participating Interest 10% (Ten Percent) in the context of improvingcommunity welfare in accordance with the mandate in the Minister of Energy and MineralResources Regulation (Permen) Number 37 of 2016 concerning Provisions for 10% (TenPercent) Participating Interest Offerings in Oil and Gas Working Areas. PT Riau Petroleummanages four 10% PIs from four oil and gas blocks by forming subsidiaries, namely PT RiauPetroleum Siak, PT Riau Petroleum Kampar, PT Riau Petroleum Mahato, and PT RiauPetroleum Rokan, the Riau Provincial Government gets the largest share with a portion of50%, while the remainder is divided among the five districts, according to the amount of oiland gas reserves in each region which has been calculated by a third party professionally.Utilization of Participating Interest 10% (Ten Percent) in the Context of Improving Welfare,among others, Siak BUMD can use the profits from the 10% PI to increase Regional OriginalIncome. Siak BUMD can use some of the profits from the 10% PI to finance communityempowerment programs, such as skills training, business capital assistance, and villageinfrastructure development. Improving the Quality of Education. Siak BUMD can use some ofthe profits from the 10% PI to finance programs to improve the quality of education, such asbuilding schools, providing scholarships, and training teachers.Keywords: Participating interest, Petroleum, Government